Stochastic Integrals and Random Sums of Power Contractions in Systemics (Journal of Informatics and Mathematical Sciences, 2021)
Stochastic integrals, random sums, random contractions, and selfdecomposable random variables constitute fundamental concepts of probability theory with significant applications in several areas of systemics. The main results of the paper are a characterization of a selfdecomposable distribution and a formulation of a Poisson random sum of power contractions. These results are established by incorporating a type of stochastic integral for a continuous in probability, homogeneous stochastic process with independent increments, and the same type of stochastic integral for a compound Poisson stochastic process with positive jumps. Interpretations of the results in treatment of risks threatening various systems are also provided.
Keywords: Stochastic integral; Random sum; Random contraction; Selfdecomposability; Risk management; Systemics